1996
DOI: 10.1111/j.1475-6811.1996.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment style and partner choice: Correlational and experimental findings

Abstract: Three studies were conducted to assess the role of attachment style in partner selection using both correlational and experimental methods. Study 1 (n = 83 couples) assessed correlations between partner ratings on attachment‐style dimensions and the relations between own and partner attachment style and relationship satisfaction. In Study 2 (n = 226) and Study 3 (n = 146), participants who varied in terms of attachment style rated the desirability of potential partners who also differed in terms of attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
66
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 36 publications
12
66
0
3
Order By: Relevance
“…Attachment theory (Hazan & Shaver, 1994) postulates three types of attachment styles: secure, anxious/ambivalent, and anxious/avoidant. Research has shown that individuals prefer partners with an attachment style similar to theirs (Frazier et al, 1996;Pietromonaco & Carnelley, 1994), although recent evidence points to a general preference for securely attached partners (Chappell & Davis, 1998). From a need-based perspective, partner selection satisfies psycho-logical needs, such as the need to belong (Baumeister & Leary, 1995), the need for intimacy (Reis & Shaver, 1988), the need for positive affect maintenance (Sedikides, Oliver, & Campbell, 1994), or the need to expand the self (A. Aron & E. Aron, 1997).…”
Section: Social Psychological Theorizing On Partner Selection: a Briementioning
confidence: 99%
“…Attachment theory (Hazan & Shaver, 1994) postulates three types of attachment styles: secure, anxious/ambivalent, and anxious/avoidant. Research has shown that individuals prefer partners with an attachment style similar to theirs (Frazier et al, 1996;Pietromonaco & Carnelley, 1994), although recent evidence points to a general preference for securely attached partners (Chappell & Davis, 1998). From a need-based perspective, partner selection satisfies psycho-logical needs, such as the need to belong (Baumeister & Leary, 1995), the need for intimacy (Reis & Shaver, 1988), the need for positive affect maintenance (Sedikides, Oliver, & Campbell, 1994), or the need to expand the self (A. Aron & E. Aron, 1997).…”
Section: Social Psychological Theorizing On Partner Selection: a Briementioning
confidence: 99%
“…For example, researchers have examined the influence of working models on the inferences people make about their partner's intentions (Collins, 1996); the interplay of distress and working models as determinants of attachment and caregiving behavior Simpson, Rholes, & Nelligan, 1992); the role of working models in partner preferences (Chappell & Davis, 1998;Frazier, Byer, Fischer, Wright, & DeBord, 1996;Pietromonaco & Carnelley, 1994), relationship stability Kirkpatrick & Hazan, 1994), and relationship dissolution (Feeney & Noller, 1992;Pistole, 1995;Simpson, 1990); and the psychodynamic organization and functioning of working models (Bartholomew, 1990;Fraley, Davis, & Shaver, 1998;Fraley & Shaver, 1997;Mikulincer, 1998;Mikulincer, Florian, & Tolmacz, 1990;Mikulincer & Orbach, 1995).…”
Section: Strengths Of An Attachment-theoretical Approachmentioning
confidence: 99%
“…Indeed, there is some evidence that individuals seek out relationships that confirm their existing beliefs about other people (Frazier, Byer, Fischer, Wright, & DeBord, 1996). However, with respect to residential mobility, this explanation seems unlikely as political mismatching most often predicts mobility away from a politically dissimilar environment and toward politically similar environments (McDonald, 2011;Motyl, 2014;Motyl et al, 2014;Tam Cho et al, 2013).…”
Section: Discussionmentioning
confidence: 99%